Produção e qualidade de sementes e raízes de cenoura em solo adubado com biofertilizante enriquecido com resíduo de terra diatomácea - Rosane Borges Mendes (2016)
Sustainable production is the focus of current agriculture, seeing as the need to better destination of the compounds generated by the industry becomes evident (PIRES; MATIAZZO, 2008).In this sense, recycling of residues in agricultural soils hasgained prominence.Among the organic waste worth mentioning those from the agricultural industry, as the generated in the production of biofuels, which generates a non-inert waste in the manufacture of oils and biofuels from diatomaceousearth.Thus, the aim of this research was to evaluate the production of carrots and soil characteristics fertilized with different proportions of enriched biofertilizer with diatomaceous earth.The experiment was conducted in the experimental area of the Instituto de Ciências Agrárias fromUFMG.Was prepared the enriched biofertilizer with different proportions of diatomaceous earth, using bovine manure, pure water not containing chlorine and the residue containing diatomaceous earth, it was obtained by anaerobic fermentation during30 days.Each treatment received the following proportions of diatomaceous earth:biofertilizer (%); 0: 100, 90:10, 80:20. 70:30 and 60:40.The statistical design used was the randomized blocks with 5 proportions and 5 repetitions, totaling 25 plots, the results were evaluated by regression analysis.The characteristics evaluated as: plants height, fresh weight and shoot dry, length and diameter of roots and total production were influenced by treatments, decreased linearly in function of increasing the proportion of diatomaceous earth, showing that diatomaceous earth can have influenced negatively, as it the treatment of witness demonstrated superior to the others who received it.For soil characteristics such as: active acidity (pH), potential acidity (H + Al), sum of bases (SB), the ability to exchange cations (T), and ability of effective cation exchange (t), organic matter (MO), carbon (C), active acidity (pH) acidity potential (M + Al), sum of bases (SB), only the pH presented quadratic regression behavior, but the values of both treatments had the pH close to neutrality that does not prevent the proper development of the plants.Already for the content of soil nutrients, root, leaf and petiole as: Nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg), sulfur (S), copper (Cu)zinc (Zn), manganese (Mn) were not observed regression effects in any of the evaluated characteristics, which can be explained by the soil already has a good level of fertility.In seed production were evaluated germination, first count, root length, shoot, seedlings and dry mass of the seedlings, and also there was no adjustment for regression, but it was observed that the treatment that received the highest dose obtained smaller average to others andthe primary umbels showed a germination and vigor upper than the secondary.Given the above, it is concluded that application of enriched biofertilizer with diatomaceous earth in different proportions did not affect the plant nutrient content and soil evaluated, and quality of seeds, but negatively affected the cultivation of carrot with the decrease in production and size of the roots.